Left atrial remodeling and cerebrovascular disease assessed by magnetic resonance imaging in patients undergoing continuous heart rhythm monitoring. (14th October 2021) - Bertelsen, L; Diederichsen, S Z; Frederiksen, K S; Haugan, K J; Brandes, A; Graff, C; Krieger, D; Hoejberg, S; Olesen, M S; Biering-Soerensen, T; Koeber, L; Vejlstrup, N; et al.
Abstract: Background: Atrial remodeling and atrial fibrillation (AF) have both been associated with cerebrovascular lesions. We wished to investigate the possible direct association between atrial remodeling and cerebrovascular disease including white matter lesions and lacunar infarcts in patients with and without atrial fibrillation (AF) as documented by implantable loop recorder (ILR). Methods: Cardiac and cerebral MRI scans were acquired in a cross-sectional study including participants ≥70 years of age with stroke risk factors (history of hypertension, diabetes mellitus, congestive heart failure and/or previous stroke) but without known AF. Cerebrovascular disease was visually rated using the Fazekas scale and number of lacunar strokes. Left atrial (LA) (see figure) and ventricular volumes and function were analyzed, and associations between atrial remodeling and cerebrovascular disease were assessed with logistic regression models. Multivariable models were adjusted for sex, age, diabetes, hypertension, heart failure and history of stroke/transient ischemic attack. The analyses were stratified according to sinus rhythm or any AF during three months of continuous ILR monitoring to account for subclinical AF. Results: Of 200 participants investigated, 87% had a Fazekas score≥1 and 45% had ≥1 lacunar infarct. Within three months of ILR implantation, AF was detected in 28 (14%) participants, while 172 (86%) had sinus rhythm only. Results are summarized in table. For participants with sinus rhythm, lower LA passive emptying fraction was associated with Fazekas score after multivariable adjustment, while LA total emptying fraction was borderline significant, and increased LA maximum and minimum volumes were associated with lacunar infarcts. There were no significant associations in patients with AF. Sensitivity analyses showed similar results with longer screening periods for AF. Conclusions: In patients free from AF as documented by ILR monitoring, we found an independent association between LA passive emptying and Fazekas score, and between atrial volumes and lacunar infarcts. This supports that atrial remodeling alone without AF is associated with an increased risk of cerebrovascular lesions. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The Innovation Fund, DenmarkThe Research Foundation for the Capital Region of Denmark